Democracia, populismo e constitucionalismo - Borgonovi, Frederico Poles (2020)
The purpose of this research aims to analyze the relation and the existing balance between democracy and constitutionalism, based on the study of populism as an element of permanent tension, in the context of the crisis of political representation that marks the 21st century, especially after the advent of the horizontal revolutions. The reasons for the crisis, the democratic imbalance and the dispute between powers served as a substratum for the development of the theme, based on the study conducted on the border between constitutional law and political science on the construction of populism as a way of making politics. Therefore, from this conceptual framework and the historical evolution of constitutionalism, the research began to trace a scenario of Brazilian democracy after the crisis of 2013, with the populist rise and the regression of fundamental rights, in order to understand to what extent constitutionalism and democracy itself are tensioned by populism in a democratic state